Estimation of Soil Carbon Stocks of Urban Freshwater Wetlands in the Colombo Ramsar Wetland City and their Potential Role in Climate Change Mitigation - Dayathilake, D.D.T.L.; Lokupitiya, E.; Wijeratne, V.P.I.S. (Wetlands, Springer, 2021)
Wetlands hold significant potential for climate change mitigation due to their high capacity to sequester atmospheric carbon dioxide (CO2). Colombo, Sri Lanka was recently declared as one of the eighteen global Ramsar wetland cities. The current study represents the first attempt to quantify soil organic carbon (SOC) stocks held by the urban freshwater wetlands in Colombo. The study focused on the extensive urban wetland ecosystems of Kolonnawa wetland and Thalawathugoda wetland park. SOC stocks were determined using three parameters: depth of soil, bulk density, and SOC concentration. Loss on ignition method was used in quantifying SOC concentrations. Average SOC stocks, up to a depth of 60 cm at Kolonnawa wetland and Thalawathugoda wetland park were estimated at 504 ± 14 t C/ha and 550 ± 23 t C/ha, respectively. Furthermore, the total SOC stock at Kolonnawa wetland and Thalawathugoda wetland park were estimated at 198,408 ± 5564 t CO2eq and 66,313 ± 2764 t CO2eq, respectively. When considering global estimates, it was found that freshwater wetlands in Colombo hold a higher SOC stock than tropical wet forests and tropical dry forests. The current study highlights the importance of urban ecosystems in mitigating the ever increasing concentrations of atmospheric CO2 .
Keywords: Soil organic carbon stock; Tropical urban wetlands; Histosols